Development of a scale to measure shared problem-solving and decision-making in mental healthcare. Issue 7 (July 2022) - Shoesmith, Wendy Diana; Abdullah, Atiqah Chew; Tan, Bih Yuan; Kamu, Assis; Ho, Chong Mun; Giridharan, Beena; Forman, Dawn; Fyfe, Sue
Highlights: An initial attempt to create a shared decision-making scale was unsuccessful. Shifting the initial focus to shared problem-solving made the scale useable. The new scale had two factors: shared problem solving and shared decision making. The scale is flexible and designed to be used in a range of situations. Shared problem-solving may be a better measure of partnership in this context. Abstract: Objectives: The aim of this study was to create a measure of collaborative processes between healthcare team members, patients, and carers. Methods: A shared decision-making scale was developed using a qualitative research derived model and refined using Rasch and factor analysis. The scale was used by staff in the hospital for four consecutive years (n = 152, 121, 119 and 121) and by two independent patients' and carers' samples (n = 223 and 236). Results: Respondents had difficulty determining what constituted a decision and the scale was redeveloped after first use in patients and carers. The initial focus on shared decision-making was changed to shared problem-solving. Two factors were found in the first staff sample: shared problem-solving and shared decision-making. The structure was confirmed on the second patients' and carers' sample and an independent staff sample consisting of the first data-points for the last three years. The shared problem-solving and decision-making scale (SPSDM) demonstrated evidence of convergent and divergent validity, internal consistency, measurement invariance on longitudinal data and sensitivity to change. Conclusions: Shared problem-solving was easier to measure than shared decision-making in this context. Practice implications: Shared problem-solving is an important component of collaboration, as well as shared decision-making.